New neolithic circular enclosures - TIRPÁK, Ján; KUZMA, Ivan (Contributions to Geophysics and Geodesy, 2021)
In 2003 and 2004, four circular enclosures, found by aerial reconnaissance, were measured by geophysical methods. The magnetometric measurements of total vector of a magnetic field were carried out by a caesium magnetometer SMARTMAG SM 4G (Scintrex, Canada). The magnetic field was prospected in duo-sensor configuration. The sensors were placed 0.3 m above ground and the horizontal distance between them was 0.5 m, which enabled the measurement of two profiles simultaneously. The magnetic field prospection was set to an interval of 5 measurements per second. The geophysical profiles distance was 0.5 m and the chosen interval provided an average pace of measurement along the profile 0.20 m. The accuracy of the measurements varies from 0.5 to 1 nT. The quoted data were statistically calculated on a basis of repeated measurements along a chosen number of profiles on the site. Standard methods incorporated in the Oasis Montaj 5.08 system (Geosoft Inc., Canada) were used for elaboration of the data measured and all the basic and derived maps.